Strengthening Indonesia's Cryptocurrency Regulation to Combat Money Laundering: A Comparative Analysis of Canada and South Korea's Approaches - Aji, Krisna Bramantyo; Nugraha, Agung Setya; Riyanto, Aditiya; Bahri, Ahmad Saefuddin; Mahmutarom (LifeSciFi, 2025)
This paper explores the challenges posed by cryptocurrency-based money laundering in Indonesia and the need for enhanced legislation to address this growing threat. It highlights the gaps in the current regulatory framework, which lacks specific provisions targeting the unique risks of digital currencies. By comparing the regulatory approaches of Canada and South Korea, the study identifies best practices that Indonesia could adopt to combat cryptocurrency-related crimes. The research emphasizes the importance of implementing targeted legislation for cryptocurrency exchanges, requiring compliance with Anti-Money Laundering (AML) and Counter-Terrorism Financing (CTF) regulations, and introducing Know-Your-Customer (KYC) procedures and real-name account policies to address the anonymity of digital assets. Furthermore, the paper advocates for strengthening international cooperation, utilizing advanced technologies like blockchain analytics, and increasing public awareness and institutional capacity to effectively tackle cryptocurrency-based money laundering. The findings underscore the need for Indonesia to adopt a more comprehensive and technologically forward-thinking legal framework that aligns with global standards to ensure a safer and more transparent digital financial ecosystem. This research contributes to the ongoing discourse on cryptocurrency regulation and offers recommendations for strengthening Indonesia's efforts in combating illicit financial activities within the digital asset space.